Profil Kompetensi Pedagogik dan Profesional Guru Bimbingan dan Konseling SMA di Kota Bandung - Nurnaifah Selvia Wardhani; Euis Farida; Eka Sakti Yudha (Indonesian Journal of Educational Counseling, 2019)
PROFIL OF PEDAGOGIC AND PROFESSIONAL COMPETENCIES OF SENIOR HIGH SCHOOL COUNSELORS IN BANDUNG CITY. This study aims to get a profile and description of pedagogic and professional competencies of guidance and counseling teachers (counselor) in Bandung. The research used the quantitative approach with survey methods. The population of this research is 127 counselors of the senior high school in Bandung. The Instrument was the development of Permendiknas No. 27 Tahun 2008 concerning Academic Qualification Standards and Counselor Competencies with ten aspects related to pedagogic and professional competencies. Data analysis techniques in this research are descriptive analysis techniques. The result of the research shows that the profile of counselors is in the competent category but in several aspects need some developed. The result of the research can be used as a need assessment for supervisor in understanding counselors competencies so that it can be used as a basis to provide guidance and counseling services effectively and efficiently.